Relationship between Overall Survival and Response or Progression‐Free Survival in Advanced Non–Small Cell Lung Cancer Patients Treated with Anti–PD‐1/PD‐L1 Antibodies. Issue 11 (November 2016) - Shukuya, Takehito; Mori, Keita; Amann, Joseph M.; Bertino, Erin M.; Otterson, Gregory A.; Shields, Peter G.; Morita, Satoshi; Carbone, David P.
ABSTRACT : Introduction : Alternative predictive end points for overall survival (OS), such as tumor response and progression‐free survival (PFS), are useful in the early detection of drug efficacy; however, they have not been fully investigated in patients with advanced NSCLC treated with anti–programmed death protein 1 (PD‐1)/programmed death ligand 1 (PD‐L1) antibodies. Methods : In a systematic review of the reported prospective clinical trials, data for response rate, median PFS, and median OS were extracted from 12 arms in 10 reported clinical trials using anti–PD‐1/PD‐L1 antibody, and their correlation was investigated. In a retrospective analysis at our institution, OS was compared according to tumor response on 5‐ to 9‐week computed tomography scans and status of being progression‐free at 8, 16, and 24 weeks by landmark analysis in 71 patients with advanced NSCLC treated with anti–PD‐1/PD‐L1 antibodies between 2013 and 2015. Results : In a systematic review, moderate correlations between median OS and median PFS ( p = 0.120, r = 0.473) and between median OS and response rate ( p = 0.141, r = 0.452) were identified using the Spearman correlation coefficient, although these correlations were not statistically significant. In a retrospective analysis of patients treated at our institution, disease control (partial response [PR]/stable disease versus progressive disease/not evaluable), and progression‐free status at 8, 16, and 24 weeks significantly predicted OS (Cox proportional hazards model, PR/stable disease versus progressive disease/not evaluable, p = 0.0104, HR = 3.041; 8‐week progression‐free yes versus no, p = 0.0183, HR = 2.684; 16‐week progression‐free yes versus no, p = 0.0036, HR = 4.009; and 24‐week progression‐free yes versus no, p = 0.0002, HR = 12.726). Conclusions : Both disease control (PR plus stable disease status) and landmark progression‐free survival were correlated with OS, with the longer interval landmark PFS being the best predictor of survival in patients with NSCLC treated with anti–PD‐1/PD‐L1 antibodies.